2015
DOI: 10.1155/2015/676748
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Intense Surface Enhanced Raman Scattering and Aggregation in the Au@Ag System

Abstract: Gold core/silver shell (Au@Ag) nanoparticles of ~37 ± 5 nm diameter generate intense SERS (λEX=785 nm) responses in solution when they interact with the SERS labels rhodamine 6G (R6G), 4-mercaptopyridine (MPY), and 4-mercaptobenzoic acid (MBA). Herein the relationship between SERS intensity, aggregation, and adsorption phenomenon isobserved by titrating Au@Ag with the above labels. As the labels adsorb to the Au@Ag, they drive aggregation as evidenced by the creation of NIR extinction peaks, and the magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Ag with the chemical stability and biocompatibility of Au. [37][38][39][40][41][42][43][44][45][46][47][48] Because Ag and Au have nearly identical crystal structures, combining the two metals to prepare hybrid particles is fairly straightforward. Most commonly, Ag and Au are combined by the formation of core-shell structures 41,47,49,50 or by alloying the two metals.…”
Section: Introductionmentioning
confidence: 99%
“…Ag with the chemical stability and biocompatibility of Au. [37][38][39][40][41][42][43][44][45][46][47][48] Because Ag and Au have nearly identical crystal structures, combining the two metals to prepare hybrid particles is fairly straightforward. Most commonly, Ag and Au are combined by the formation of core-shell structures 41,47,49,50 or by alloying the two metals.…”
Section: Introductionmentioning
confidence: 99%
“…47 Other tests have found that new roughened surfaces, aggregated colloidal suspensions, electrodes, cold substrates, and metal-island films and colloids, silver island films and silver coated beads were appropriate for LSPR enhancement of SERS. 48,[49][50][51][52] PART THREE: THEORY ON SURFACE ANALYSIS…”
Section: Surface Enhanced Raman Scattering (Sers)mentioning
confidence: 99%
“…Equation 3.1.1 shows that the extinction cross section depends on two factors: (1) the dielectric field of the environment and (2) on the volume of the (nano) particle. 51 This is referred to as the long-wavelength approximation of the dipolar resonance. By applying this formula, Mie assumed that the plasmon resonance had to be centered on a light frequency composed by a real part, of a complex dielectric, with twice the magnitude of the dielectric constant of the medium, i.e.…”
Section: Mie Theory and The Raman Scattering Cross Section Of Gold Npsmentioning
confidence: 99%
See 2 more Smart Citations